Proceedings of the 33rd Annual ACM Conference Extended Abstracts on Human Factors in Computing Systems 2015
DOI: 10.1145/2702613.2732769
|View full text |Cite
|
Sign up to set email alerts
|

Be Informed and Be Involved

Abstract: User's confidence in machine learning (ML) based decision making significantly affects acceptability of ML techniques. In this work, we investigate how uncertainty/correlation affects user's confidence in order to design effective user interface for ML-based intelligent systems. A user study was performed and we found that revealing of correlation helped users better understand uncertainty and thus increased confidence in model output. When correlation had the same trend with performance, correlation but not u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…For example, Hoffman et al [74] presented metrics for explainable systems that are grounded in the subjective evaluation of a system (e.g., user trust, satisfaction, and understanding). Zhou, et al [65,75] investigated factors such as uncertainty and correlation that affect user confidence in ML-informed decision-making. Zhou et al [64] found that the explanation of influence of training data points significantly affected user trust in ML-informed decision-making.…”
mentioning
confidence: 99%
“…For example, Hoffman et al [74] presented metrics for explainable systems that are grounded in the subjective evaluation of a system (e.g., user trust, satisfaction, and understanding). Zhou, et al [65,75] investigated factors such as uncertainty and correlation that affect user confidence in ML-informed decision-making. Zhou et al [64] found that the explanation of influence of training data points significantly affected user trust in ML-informed decision-making.…”
mentioning
confidence: 99%
“…Research in HCI has started to focus on uncertainty visualization and communication recently as well, for the exploration of personal genomics data [29], data analysis [5], machine learning [15,36], bus arrival predictions [13], range anxiety in electric cars [12] and other applications.…”
Section: Visualization Of Uncertaintymentioning
confidence: 99%